An action-observation method for studying social perception: a mini-review - Liu, Manlu; Enns, James T. (Frontiers in Psychology, 2024)
An important aspect of any social interaction involves inferring other people's mental states, intentions, and their likely next actions, by way of facial expression, body posture, eye gaze, and limb movements. An actor's production of actions during social interactions and the observer's perception of these actions are thus closely linked. In this review, we outline an actionobservation methodology, which not only allows for separate analyses of production and perception, but also promotes the study of the dynamic interaction between these two sides of every social exchange. We review two lines of research that have benefited from its application. The first line focuses on individuals performing tasks alone and the observation of their actions by other individuals in order to make inferences about their attentional states. The second line of study focused on pairs of individuals performing collaborative tasks in naturalistic settings and the observation of these performances by other individuals. We offer several suggestions for how this methodology can be extended to improve on the limitations of the present studies, as well as some suggestions of how to use this methodology to venture into new territory. Our aim is to inspire future research applications of this methodology in order to advance our understanding of social action production and perception.